Manajemen Keragaman dan Kesejahteraan Tenaga Kerja dalam Perspektif Regulasi Ketenagakerjaan di Indonesia - Rahma Eka Rianti; Fariska Maulidah Hikmawati; n Nur Oktaviani; Pupung Purnamasari (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study explores the relationship between diversity and workforce well-being in Indonesia using a literature review approach. Workforce diversity encompasses various elements such as age, gender, culture, and types of employment, which if managed effectively can enhance creativity and productivity. However, without inclusive management strategies, diversity may lead to discrimination and imbalance. Moreover, employee well-being is influenced not only by wages but also by social protection, legal safeguards, and work-life balance. National regulations, such as the Labor Law and its implementing rules, reflect formal efforts to protect workers, yet their implementation remains insufficient, particularly for vulnerable groups such as women and contract workers. This study highlights the importance of collaboration among the government, companies, and workers in creating fair and sustainable workplaces. It also emphasizes the need to strengthen regulations and supervision to achieve comprehensive workforce well-being.